Exploring the Impact of Digital HR Practices on Employee Performance and Organizational Efficiency in the Pharmaceutical Sector (Journal of Carcinogenesis, 2025)
Analyse how digital HR applications have affected pharmaceutical industry performance management, e-recruitment, retention, training, and job satisfaction rates. Data from 275 employees at various pharmaceutical companies are analysed in this cross-sectional study, which makes use of quantitative approach. Using IBM SPSS Statistics, researchers performed descriptive and inferential statistical studies to identify the key factors that influence employee performance and the results achieved by the company.Excellent employee performance is substantially predicted by the adoption of digital HR technology, employee participation, and satisfaction with these tools (p < 0.05). In addition, the size of the business was shown to be a significant factor in explaining both organisational efficiency and overall utilisation of HR tools (p < 0.01). Larger firms were found to be more efficient and had higher reports of using digital HR tools. There was a little correlation between gender and employee performance, and younger employees were more likely to utilise digital HR tools.In larger companies with better investments in technology, the results show that digital HR policies, when implemented well, boost organisational efficiency and employee performance. The authors admit that the study is limited by its cross-sectional design, which prevents causal findings, and by the possibility for response bias resulting from self-reported performance data. Nevertheless, the research makes important contributions. To assess the long-term consequences of digital HR technology and the influence of moderating factors like leadership style and culture, longitudinal studies would be useful. Human resource professionals looking to boost employee output and the company's bottom line should use the study's practical advice on how to implement digital HR solutions.